Pengaruh Kunjungan Wisatawan, Inflasi Dan Kurs Dollar Amerika Serikat Terhadap Nilai Ekspor Kerajinan Bambu Provinsi Bali - Astuti, Ni Kadek Dewi; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 2, Februari 2016 (pp. 216 - 315), 2016)
Commodities crafts including export commodities seeded in Bali P rovince. One of the handicraft commodities exported by the Bali Province is bamboo handicraft. This study aims to determine an analyzed the impact of tourist visits, inflation and the exchange rate of the US dollar against the value of export of bamboo handicraft Bali Province simultaneously and partially. The purpose of this research to determine which variables are the dominant influence on the value of export of bamboo handicraft Bali Province. The result showed that the variables simultaneously tourist visits, inflation and the US dollar exchange rate significantly influence the value of export of bamboo handicraft Bali Province. US dollar exchange rate variable positive and significant effect, variable inflation significant negative effect on the value of export of bamboo handicraft Bali Province 1994-2014 year.  The dominant variable influence on the export of bamboo handicraft Bali Province is variable US dollar exchange rate.
Keywords: bamboo handicraft export; tourist arrivals; inflation; US dollar exchange rate